2012
DOI: 10.1371/journal.pone.0032090
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Randomized Clinical Trials in the Treatment of Human Brucellosis

Abstract: BackgroundBrucellosis is a persistent health problem in many developing countries throughout the world, and the search for simple and effective treatment continues to be of great importance.Methods and FindingsA search was conducted in MEDLINE and in the Cochrane Central Register of Controlled Trials (CENTRAL). Clinical trials published from 1985 to present that assess different antimicrobial regimens in cases of documented acute uncomplicated human brucellosis were included. The primary outcomes were relapse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 60 publications
(182 reference statements)
2
108
1
1
Order By: Relevance
“…Thirteen studies comparing tetracycline associated with rifampin and tetracycline associated with gentamycin showed superiority of treatment with aminoglycosides (AII) 25 . These findings were confirmed by two more systematic reviews 26,27 . In the same year, a systematic review published by the Cochrane Group suggested the same treatment combination, however, with streptomycin as the aminoglycoside of choice 28 .…”
Section: Treatmentsupporting
confidence: 55%
“…Thirteen studies comparing tetracycline associated with rifampin and tetracycline associated with gentamycin showed superiority of treatment with aminoglycosides (AII) 25 . These findings were confirmed by two more systematic reviews 26,27 . In the same year, a systematic review published by the Cochrane Group suggested the same treatment combination, however, with streptomycin as the aminoglycoside of choice 28 .…”
Section: Treatmentsupporting
confidence: 55%
“…8 Some patients were put on trimethoprim-sulfamethoxazole (160/800 mg BD) plus doxycycline. 7 Of the patients, 41% recovered fully, whereas 21% had a relapse that necessitated another course of oral treatment plus intramuscular streptomycin. Another one-third of the patients recovered but had sequelae, which included difficulty in walking and pain because of osteomyelitis or discitis from spinal infections.…”
Section: Introductionmentioning
confidence: 97%
“…7 If they had localized disease, they were prescribed the oral regimen as above plus intramuscular streptomycin (1 gm daily). 8 Some patients were put on trimethoprim-sulfamethoxazole (160/800 mg BD) plus doxycycline.…”
Section: Introductionmentioning
confidence: 99%
“…12 Although there are some cases seriesly reporting successful outcomes with quinolone including regimen, it is not supported by randomized clinical studies. 13,14 Even so, the long duration of unresponsiveness to doxycycline plus rifampicin pushed us also to add ciprofloxacin to the treatment according to the available antibiotic properties and reported case series. However, the success achieved with the applied therapy should be supported by randomized studies to recommend quinolones in the first-line therapy for cyst infections.…”
Section: Discussionmentioning
confidence: 99%